The evolution of the gender wage gap in Colombia: 1994 and 2010 - Luz Karime Abadía Alvarado; Sara De la Rica (Cuadernos de Economía, 2020)
This paper studies the evolution of the gender wage gap in Colombia at different points of wage distributions. Using DiNardo, Fortin, and Lemieux’s (1996) decomposition, we find that the enormous increase in female workers’ educational achievement has helped to reduce the gender gap, mainly at the top of the wage distribution. However, this effect has been countered by the reduction in the proportion of female workers in the public sector and those with indefinite contracts. Moreover, using the Arellano et al. (2017) methodology, we estimate the adjusted gender wage gap whilst controlling for sample selection. In both analysed years, our main finding was a clear glass-ceiling pattern that was slightly reduced in 2010.